Modelling and Coordination of a Swarm of Quadrotors Using Lagrange Dynamics and Potential Functions - (:unkn) unknown (IEEE, 2019)
In this article we develop an energy based model for the dynamics of a swarm of quadrotors using Lagrangian approach. Both the individual quadrotor dynamics and the interaction dynamics between the agents in the swarm are modeled within the framework. Artificial potential energy and the corresponding potential forces are utilized for modeling the interaction between the quadrotors. Various simulations are performed to illustrate the viability and effectiveness of the developed swarm model. The kinetic and potential energy of the swarm is also illustrated.
Keywords: swarms; multi-agent dynamic systems; quadrotors; quadcopters; UAVs; distributed coordination and control; potential functions; Lagrangian dynamics; energy based modeling